Weight variability, physical functioning and incident disability in older adults - Katie J. McMenamin; Tamara B. Harris; Joshua F. Baker (Wiley, 2023)
Abstract Background This study aimed to determine if greater variability in body mass index (BMI) is associated with declines in physical functioning and incident disability in older adults. Methods Included were participants from the Health, Aging and Body Composition Study who had semi‐annual BMI data during the first 3 years of follow‐up. Participants were categorized into quintiles of BMI variability, using two methods. The first method used average successive variability, whereas the second method adjusted these values to remove the variability due to net change in BMI over the 3‐year period. Linear regression was used to assess the relationship between the two measures of BMI variability and net changes in BMI, fat mass index, appendicular lean mass index, and Health, Aging and Body Composition Physical Performance Score during the first 3 years of the study. Cox proportional hazard models were used to assess the relationship of BMI variability with the subsequent incidence of new disability, adjusting for confounding factors. Results Among 2121 participants, those in the highest BMI variability quintile were more likely to lose both body mass (β: −0.086 [95% confidence interval, CI: −0.133, −0.040], P < 0.01) and fat mass (β: −0.059 [95% CI: −0.117, −0.002], P = 0.04) and had greater declines in physical performance score (β: −0.094 [95% CI: −0.162, −0.026], P < 0.01) compared to participants with the least variability in BMI. Participants with high BMI variability also had higher rates of incident disability (hazard ratio: 1.36 [95% CI: 1.07, 1.72], P = 0.01), independent of net BMI change. Conclusions BMI variability in older adults is associated with decline in physical performance and incident disability. This relationship cannot be explained by net weight loss alone, supporting it as an independent feature of frailty.